The Incidence and Clinical Implications of Congenital Defects of Atlantal Arch - Kwon, Jong Kyu (The Korean Neurosurgical Society, 2009)
OBJECTIVE: Atlantal arch defects are rare. Few cadaveric and imaging studies have been reported on the variations of such anomalies. Our goal in this study was to examine the incidence and review the clinical implications of this anomaly. METHODS: A retrospective review of 1,153 neck or cervical spine computed tomography (CT) scans was performed to identify patients with atlantal arch defects. Neck CT scans were performed in 650 patients and cervical spine CT scans were performed in 503 patients. Posterior arch defects of the atlas were grouped in accordance with the classification of Currarino et al. In patients exhibiting this anomaly, special attention was given to defining associated anomalies and neurological findings. RESULTS: Atlantal arch defects were found in 11 (11/1153, 0.95%) of the 1,153 patients. The type A posterior arch defect was found in nine patients and the type B posterior arch defect was found in two patients. No type C, D, or E defects were observed. One patient with a type A posterior arch defect had an anterior atlantal-arch midline cleft (1/1153, 0.087%). Associated cervical spine anomalies observed included one C(6-7) fusion and two atlantal assimilations. None of the reviewed patients had neurological deficits because of atlantal arch anomalies. CONCLUSION: Most congenital anomalies of the atlantal arch are found incidentally during investigation of neck mass, neck pain, radiculopathy, and after trauma.